A Customizable Information Quality Activity in Business and Management Courses: Recommendations for Research. (March 2023) - Gerard, Joseph G.; Lederman, Reena E.; Greeley, Jack P.
As business and management instructors, we increasingly struggle with student inattention to information accuracy and quality in our courses, especially when student-based research is required and misinformation is more prevalent. Without the time to teach information literacy (IL) skills, we created a series of information sourcing (IS) prompts that were small and flexible enough to be deployed anywhere we might need IL reinforcement. We describe this "IS plug-in, " share challenges surrounding its creation and successful implementation across multiple courses, and explain its grounding in information literacy theory. We then provide insights and recommendations for future management education research that arose from experiences with the unique IS plug-in approach and in-depth application of new research in IL. We provide recommendations for expanding the IL Framework's use and measurement, and improving our understanding of authority and information versus belief.